The Social Structure and Ideology of the Rebel Movement in Yakutia during 1921–1922 - E.P. Antonov; V.N. Antonova (Ученые записки Казанского университета: Серия Гуманитарные науки)
As part of the complex research on the Yakut anti-Soviet rebel movement in 1921–1922, which rose to the national level, the social structure and ideology of the rebels have been considered. It has been found that the poor, farmhands, and peasants of medium welfare formed the basis of the movement. Russian officers were responsible for the military command. The ideological guidance was performed by the intelligentsia. The financial support was provided by the merchants. Having analyzed the programs, charters, appealings, private letters, and other papers, we have made the following conclusions: most rebels were for the All-Russian Constituent Assembly, building of the national state by providing provincial autonomy, as well as the multiparty system and democratic liberties. They developed the executive branch in the form of an institute for district intendants and volost, nasleg and village administrations. In the sphere of economy, it was supposed to establish the share system according to the labor rate and to retain the status of a free-trade zone on the coast of the sea of Okhotsk to cope with the goods famine. The available factual material shows the transformation of the aboriginal people of Yakutia into an active subject of the historical process. The reconstruction of the political platform of the rebel movement is a reflection of the period of anticipated and hard development of the ideas about nation building.